Radiographic evaluation of temporomandibular joint in patients with posterior direct restorations - I. N. Bagdasarova; A. A. Gevorkyan; O. V. Pilshchikova; N. N. Fedotova; A. S. Karnaeva; L. A. Kozhevnikova; V. M. Slonova (Эндодонтия Today)
Relevance. The process of tooth wear and direct restorations can progress and cause dysfunction of the temporomandibular joint (TMJ), the assessment of which is quite effective using cone beam computed tomography (CBCT).The aim is to study of the morphological parameters of the condyles and their relationship with the articular fossa of the TMJ using CBCT in patients with direct restorations in the masticatory region of the upper and lower jaws.Materials and methods. We studied 26 CBCT (18 women and 8 men) with a ratio of teeth with I class, without clinical symptoms and not undergoing orthodontic treatment, with an average age of 45.6 years. TMJ was evaluated by angular and linear parameters on three sections. Results. The entire space was larger on the right than on the left, however, this difference was only statistically significant for the superior and posterior spaces. The center of the condyle was shifted anteriorly more to the left than to the right, and also, the head of the condylar process had a more inclined anteriorly to the left than to the right. At coronal sections, the medial-lateral angulation was the same for both sides, as well as the distance from the center of the condyle to the mid-sagittal plane. Conclusions. The features and the absence of clinical symptoms showed potential changes in TMJ on CBCT in patients with direct restorations that have been functioning for more than two years.